Impact of colombia ́s foreign debt in the balance of payments for the period 2007-2012 (2013)
This essay is the result of an investigation documentary about the impact of Colombia's foreign debt in the Balance of Payments for the period 2007-2012. In the context of the current situation of the country, was selected this topic because the External Public Debt is one of the most important sources of financing Government determined to meet the needs arising in the country as investment for the development of the governmental policies and goals. Linked to this, the Balance of Payments is a major component in the economic analysis which can determine the need for starting the deficit debt arises. Is how there is some vulnerability in the Balance of Payments due to the behavior of the External Public Debt, which has been presented an increasing trend impacting the liabilities of the capital account in the balance of payments.